ALGORITMA BLOWFISH UNTUK MENINGKATKAN KEAMANAN DATABASE MYSQL - Harlen Gilbert Simanullang; Arina Prima Silalahi (Universitas Methodist Indonesia, 2018)
The limitations of humans to maintain the security and confidentiality of stored data can have a bad impact if it is used by unauthorized parties. One way to secure shipping is to convert data into one that is not understood by encoding and insertion using cryptographic techniques. Cryptography is the study of system security, where the system needs to be secured from interference or threats from irresponsible parties. One of the cryptographic algorithms is the Blowfish Algorithm. The Blowfish algorithm is a modern cryptographic algorithm symmetrical key shaped block cipher. The Blowfish algorithm is quite simple but strong enough because it has a long key space, making it difficult to attack. Encryption is done by using a certain key, so as to produce ciphertext (files that have been encrypted or encoded) that cannot be read or understood. The ciphertext can be restored as if it was decrypted using the same key when encrypting the file. The key length used can affect the security of the algorithm. The decryption flow is almost the same as the Blowfish Algorithm encryption, except in the P-array (P1, P2, …… .., P18) done by invading. Information of a system is certainly stored in a database that is always possible to attack, but using cryptography then the problem can be overcome. By using the Blowfish algorithm, information security in a MySQL database can be improved.